A Study on the Impact of Infrastructure Elements on Aspiring Home Buyers in the National Capital Region - Mittal, Rashi; R., Ananta Singh (Indian Journal of Marketing, 2014)
While the most decisive factor for purchasing residential real estate has largely been location, location, and location, there are other factors such as price, amenities, and the developer repute, that also prove to be decisive for a potential home buyer in making the final choice. However, in the current scenario, elements such as water, energy, transportation, and other variables have assumed considerable significance for the prospective clients seeking to purchase a place to dwell in. This present scenario is largely attributed to the fact that certain premium townships across India, which were once most sought after in the initial stages of launch, post handover, the end users had multiple grievances pertaining to their surrounding support systems such as road, electricity, health care, and so forth. This set of interrelated support systems that makes life easier and contributes to the functioning of the society and its activities is termed as infrastructure. The simplified definition of infrastructure is that it is a framework under which various systems and their components operate and deliver service to the end users. Human beings, over a period of time, have created support frameworks in order to sustain themselves in and around their dwellings. From establishing living spaces in and around sources of food and water, in the present times, accessibility and proximity to places of work have taken precedence. Thus, an assessment of the findings of the study throws light on why infrastructure is slowly becoming a high-priority factor in influencing the home buyer's mindset.